EXPERIMENTAL ANALYSIS OF FIN TUBE AND BARE TUBE TYPE TUBE-IN-TUBE HEAT EXCHANGER - Kamalesh S. Kulkarni; Ravindra M. Ghodke (International Journal of Innovations in Engineering Research and Technology, 2021)
Heat exchangers are the devices that facilitate the exchange of heat between the two fluids that are at different temperatures while keeping them from mixing with each other. In bare tube heat exchanger, the heat transfer rate is minimum so in order to increase the heat transfer rate different types of fins are used. The rate of heat transfer depends on the surface area of the fin. Rectangular and circular type fins are popular choices for transferring the heat from the primary surface of heat exchanger. In this paper, heat transfer rate and fin effectiveness for rectangular and circular fins were analysed for parallel flow and counter flow arrangement and comparison is done with bare tube (tube without fin) heat exchanger. Performance of rectangular fin is efficient than the circular fin.